Extreme sustainability rhetoric and sustainable development - Nunes, Mauro Fracarolli; Park, Camila Lee (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book considers the nature, causes and consequences of extreme pro- and anti-sustainability rhetoric, exploring how and why the expressions of radical views on sustainability-related themes may prevent real sustainable development. Following a thorough introduction on sustainability rhetoric, on dialogue and on the role played by ideologies in the building of environmental beliefs, Fracarolli Nunes and Lee Park examine positions and statements expressed or made by individuals, companies, governments, and NGOs in the last decades. The outcomes of these considerations lead to the classification of expressions in different categories of sustainability rhetoric, laying the groundwork for the development of a 'sustainability spectrum': a metric for the level of radicalization of sustainability positions, which ranges from apocalyptic views to ultimate denial. Through the combination of historical perspectives, theoretical frameworks, and conceptual developments, this book provides a foundation for a more informed and productive dialogue between radically opposing views on sustainability issues. This volume will be of great interest to students, scholars and practitioners researching and working in the areas of environmental communication and media, environmental politics and sustainable development"--
Keywords: Sustainable development; Communication in the environmental sciences; BUSINESS & ECONOMICS / Development / Sustainable Development; LANGUAGE ARTS & DISCIPLINES / Rhetoric; POLITICAL SCIENCE / Public Policy / Environmental Policy